Red internacional para potenciar la investigación científica en torno al uso del hidrógeno y amoniaco como vectores energéticos en Chile - (:unkn) unknown (My University, 2025)
The project titled RED INTERNACIONAL PARA POTENCIAR LA INVESTIGACION CIENTIFICA EN TORNO AL USO DEL HIDROGENO Y AMONIACO COMO VECTORES ENERGETICOS EN CHILE (International Network to Enhance Scientific Research on the Use of Hydrogen and Ammonia as Energy Carriers in Chile) which will be submitted to the call for fostering international collaboration for research institutions in 2023 is presented to provided ANID supports the generation and strengthening of networks to consolidate international connections between scientific, technological research, and innovation institutions in Chile and foreign institutions that contribute with an interdisciplinary approach to developing and strengthening international linkage capabilities in different areas related with hydrogen and ammonia as neutral carbon fuels and their derivatives regarding their applications in Chile. In particular, the proposed network revolves around hydrogen and ammonia as energy carriers, which has become a state policy in recent years and represents a significant opportunity to fund related research in this field. Considering this context, the funds will be used to develop a collaboration network with confirmed Colombian researchers (Universidad del Norte), American researchers (Colorado State University), Spanish researchers (Universidad Politecnica de Valencia, to be confirmed), and, obviously, Chilean researchers( Universidad de Magallanes, Universidad Austral de Chile and USM).
Keywords: hidrógeno; amoniaco